2012
DOI: 10.1371/journal.pone.0031334
|View full text |Cite
|
Sign up to set email alerts
|

A Double-Blind, Placebo-Controlled, Randomized, Clinical Trial of the TLR-3 Agonist Rintatolimod in Severe Cases of Chronic Fatigue Syndrome

Abstract: BackgroundChronic fatigue syndrome/myalgic encephalomyelitis (CFS/ME) is a severely debilitating disease of unknown pathogenesis consisting of a variety of symptoms including severe fatigue. The objective of the study was to examine the efficacy and safety of a TLR-3 agonist, rintatolimod (Poly I: C12U), in patients with debilitating CFS/ME.Methods and FindingsA Phase III prospective, double-blind, randomized, placebo-controlled trial comparing twice weekly IV rintatolimod versus placebo was conducted in 234 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 39 publications
3
54
0
2
Order By: Relevance
“…Another variant, poly(I:C 12 U) (rintatolimod) has been developed for its favourable toxicity profile, which is probably due to an inability to activate MDA5. It is being clinically evaluated for the treatment of chronic fatigue syndrome 43 .…”
Section: Empirical Discovery Of Agonists For Nucleic Acid Sensorsmentioning
confidence: 99%
“…Another variant, poly(I:C 12 U) (rintatolimod) has been developed for its favourable toxicity profile, which is probably due to an inability to activate MDA5. It is being clinically evaluated for the treatment of chronic fatigue syndrome 43 .…”
Section: Empirical Discovery Of Agonists For Nucleic Acid Sensorsmentioning
confidence: 99%
“…Some agonists of the TLRs or NLRs are used as vaccine adjuvants. The poly I:C (TLR3 agonists) (Strayer et al, 2012), flagellin (TLR5 agonists)(Liu et al, 2011b), imidazoquinolines (TLR7 and TLR8 agonists) (Raman et al, 2012), CpG (TLR9 agonists) (Gupta and Cooper, 2008) are tested as vaccine adjuvants in human. The adjuvant AS04 containing ingredients derived from TLR4 agonists is licensed for use in human vaccines (Rappuoli et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…12 The investigational immuno-modulatory doublestranded RNA drug rintatolimod (Ampligen®; Hemispherx Biopharma, Inc.) produced objective improvement in exercise tolerance and other endpoints in a phase 3 prospective, double-blind, randomized, placebo-controlled trial of 234 subjects with longstanding, debilitating ME/CFS. 13 There are several pro-inflammatory cytokines identified that are significantly elevated in samples from 200 ME/CFS patients compared with 400 ageand gender-matched controls, and that correlate with illness severity. It's an indicator that what you are seeing is real.…”
Section: View Pointmentioning
confidence: 99%